Liberare il molteplice Una valenza etica della letteratura (ENTHYMEMA, 2012)
This essay analyses how literature, as memorial pietas and affectively connoted knowledge, gives shape to a form of opposition or inclusion of the economic dimension. In particular, this is possible because of its ability of freeing the multiplicity of the world from the suffocating hug of the so-called “single thought”. These ethical reflections lead us to a philosophy of literature, rather than to a pragmatics of the literary text.